1979
DOI: 10.1128/iai.24.3.932-938.1979
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and intracellular killing of pathogenic yeasts by human monocytes and neutrophils

Abstract: The kinetics of phagocytosis and killing of four fungal forms with varying virulence by two types of phagocytic cells was examined. Human monocytes ingested Saccharomyces cerevisiae, Candida tropicalis, and the blastospores of Candida albicans more rapidly than did human neutrophils. There was no difference in the rate of phagocytosis of C. albicans pseudohyphae by these two cell types. Intracellular killing of each of the four fungal forms was consistently and significantly more rapid by monocytes than by neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…[12], whereas Rodey et al [15] found equal functional ciipacitics LHHI Scluiit [16] an even more aciive bchi.i\iour of monocytes than granulocytes in the phagocytosis of Candida species. So far.…”
Section: Discussionmentioning
confidence: 99%
“…[12], whereas Rodey et al [15] found equal functional ciipacitics LHHI Scluiit [16] an even more aciive bchi.i\iour of monocytes than granulocytes in the phagocytosis of Candida species. So far.…”
Section: Discussionmentioning
confidence: 99%
“…albicans killing assay. Phagocytosis and intracellular killing of C. albicans by PM4 and monocytes were assessed by a previously described fluorochrome (acridine orange) microassay (44) modified for the purposes of this study. A clinical isolate of C. albicans was cultured for 18 h at 37°C in Sabouraud 2% dextrose broth (Difco Laboratories, Detroit, Mich.).…”
Section: Methodsmentioning
confidence: 99%
“…A mixture of opsonized C. albicans (2 x 106 blastospores in 100 ,u of GHBSS) and phagocytes (5 x 105 cells in 100 ,u of GHBSS) was incubated for 30 min at 37°C in a shaking incubator (250 rpm). After the pellets were washed and resuspended in 1.0 ml of GHBSS, 200-pAl portions of the final suspensions were deposited onto glass cover slips, incubated for 60 min at 37°C, and then stained with acridine orange (44). Preparations were examined under a 100x oil immersion objective with a UV fluorescence microscope (Leitz, Wetzlar, Federal Republic of Germany).…”
Section: Methodsmentioning
confidence: 99%
“…5 ml saline, and the suspension was cultured on a standard Mullar Hinton agar plate. After 24 h incubation at 37ЊC, the number of colonies was counted to determine the number of viable leucocyte-associated bacteria [12][13][14].…”
Section: Activity Of Alveolar Macrophagesmentioning
confidence: 99%